Neostigmine for the Treatment of Acute Hepatic Encephalopathy with Acute Intestinal Pseudo-obstruction in a Cirrhotic Patient - Park, Chang-Hwan (The Korean Academy of Medical Sciences, 2005)
We treated a 49-yr-old man with neostigmine, who had liver cirrhosis, acute hepatic encephalopathy, and acute intestinal pseudo-obstruction. He was admitted in a state of hepatic confusion. On physical examination, the abdomen was distended; and bowel sound was absent. Plain abdomen film revealed multiple air-fluid levels and distention of bowel loops. Initially, we gave him lactulose enemas every 6 hr for one day without improvement in his mental state. Furthermore, he became to a state of coma. Therefore, we gave him 0.5 mg of neostigmine subcutaneously to improve his peristaltic movement, and 2 L of polyethylene glycol electrolyte solution through a nasogastric tube for 4 hr to reduce the production and absorption of gut-derived toxins of nitrogenous compounds. After these treatments, the venous ammonia level decreased to the normal range within 12 hr, and the coma disappeared after 2 days. We suggest that neostigmine may be one of the most effective treatments to initiate peristaltic movement and bowel cleansing in cirrhotic patients with acute hepatic encephalopathy and acute intestinal pseudo-obstruction.